Judges 3: Collapse of Covenant - Dicker, Yehuda (Iggrot Ha'Ari, 2022)
Many of the narratives in Sefer Shofetim, the book of Judges, follow a narrative cycle: Bnei Yisrael, the Children of Israel, sin, God sends a foreign nation to oppress them, and the people cry out to God, who then sends them a savior. Following the savior’s death, Bnei Yisrael repeat this cycle. This essay will firstly analyze the significance of the Ehud-Eglon episode found in the third chapter of Judges in which Ehud artfully deceives and murders the Moabite King, Eglon, thereby extracating Bnei Yisrael from an oppressive foreign power. I will then explore what the chapter communicates about the larger national condition of the Israelites, and how the characters of Otniel, Ehud, and Shamgar each shed a unique light on the Bnei Yisrael’s deteriorating religious and political stature